Comprehensive Physiology 1995
DOI: 10.1002/cphy.cp110115
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Selected Endocrine Systems in Aging Processes

Abstract: The sections in this article are: Hormones and Aging: An Overview Hormonal Alterations During Aging Gonadal Steroids Adrenal Steroids Growth Hormone Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 209 publications
0
4
0
Order By: Relevance
“…We recognize, however, that higher renal medullary eNOS protein abundance is seen in young adult females [31], which is presumably responsible for the findings of Reckelhoff et al [32] who observed more eNOS in whole kidney homogenates from young adult female versus male rats. Since estrogen levels tend to decline with advanced age in females [33], it seems unlikely that estrogens are directly responsible for the maintenance of the constitutive NOS enzymes in the old female kidney. We suggest an alternative mechanism that may explain the gender differences in renal NOS expression in the aging kidney, based on the development of CRD as the initiating factor in reduced renal NOS expression, see below.…”
Section: Discussionmentioning
confidence: 99%
“…We recognize, however, that higher renal medullary eNOS protein abundance is seen in young adult females [31], which is presumably responsible for the findings of Reckelhoff et al [32] who observed more eNOS in whole kidney homogenates from young adult female versus male rats. Since estrogen levels tend to decline with advanced age in females [33], it seems unlikely that estrogens are directly responsible for the maintenance of the constitutive NOS enzymes in the old female kidney. We suggest an alternative mechanism that may explain the gender differences in renal NOS expression in the aging kidney, based on the development of CRD as the initiating factor in reduced renal NOS expression, see below.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that appropriate models are carefully selected. Virtually all 'aged' animals (i.e., rodents) are obese; therefore, interpretation of the results may be complicated by marked changes in the endocrine system which are known to occur as weight increases [19]. To exclude questionable outcomes, the animals chosen for the present studies were the Fischer 344 !…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a progressive age‐related impairment in energy expenditure. The ageing process is associated to decreased energetic requirements due to a reduction in basal metabolic rate (Goran & Poehlman 1992) and physical activity (Starling 2001), as well as hormonal alterations, mainly of gonadal and growth hormones (Nelson 1995). It is extensively described that food restriction leads to a decrease in the energy expenditure as a mechanism of energy conservation, which is elementary for the animal survival (Luz & Griggio 1991, Munch et al.…”
Section: Discussionmentioning
confidence: 99%